CD18 Regulates Monocyte Hematopoiesis and Promotes Resistance to Experimental Schistosomiasis - Souza, Camila O. S.; Espíndola, Milena S.; Fontanari, Caroline; Prado, Morgana K. B.; Frantz, Fabiani G.; Rodrigues, Vanderlei; Gardinassi, Luiz G.; Faccioli, Lúcia H. (Frontiers in Immunology, 2018)
Infection with Schistosoma mansoni causes a chronic parasitic disease that progress to severe liver and gastrointestinal damage, and eventually death. During its development into mammalian hosts, immature schistosomula transit through the lung vasculature before they reach the liver to mature into adult worms. A low grade inflammatory reaction is induced during this process. However, molecules that are required for efficient leukocyte accumulation in the lungs of S. mansoni-infected subjects are unknown. In addition, specific leukocyte subsets that mediate pulmonary response during S. mansoni migration through the lung remain to be elucidated. β2 integrins are fundamental regulators of leukocyte trans-endothelial migration and function. Therefore, we investigated their role during experimental schistosomiasis. Mice that express low levels of CD18 (the common β2 integrin subunit) and wild type C57BL/6 mice were subcutaneously infected with S. mansoni cercariae. Cellular profiles of lungs and livers were evaluated in different time points after infection by flow cytometry. Low levels of CD18 affected the accumulation of patrolling Ly6Clow, intermediate Ly6Cinter monocytes, monocyte-derived macrophages and monocyte derived-dendritic cells in the lungs 7 days after infection. This correlated with increased TNF-α levels. Strikingly, low CD18 expression resulted in monocytopenia both in the peripheral blood and bone marrow during acute infection. After 48 days, S. mansoni worm burdens were higher in the hepatic portal system of CD18low mice, which also displayed reduced accumulation of patrolling Ly6Clow and intermediate Ly6Cinter, but not inflammatory Ly6Chigh monocytes. Higher parasitic burden resulted in increased granulomatous lesions in the liver, increased egg deposition and enhanced mortality. Overall, our data point for a fundamental role of CD18 for monocyte hematopoiesis during infection, which promotes an efficient host response against experimental schistosomiasis.